If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 12 = -36 Reorder the terms: 12 + -2x = -36 Solving 12 + -2x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2x = -36 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = -36 + -12 -2x = -36 + -12 Combine like terms: -36 + -12 = -48 -2x = -48 Divide each side by '-2'. x = 24 Simplifying x = 24
| 6(-2z+5)=19z+16 | | 4*(3x-4)=44 | | 4x+15=2x+14 | | =12(p+4) | | 5x+20=2x-6 | | 6y-12-3y-3=8 | | 3m*n= | | (X/12)=50/6x) | | (-7/6)(-8/9) | | 4x+23=4 | | (5y)(4x+3y)=0 | | 100+2x-y+x=180 | | (6x+-4y)(5x+-3y)=0 | | 6y=6-12x | | x^2-20x+180=0 | | 2002/26 | | 33x-10y=70 | | 8x-(-10x)= | | 14/56=x/100 | | (8m-3)=24 | | I=0.2n | | 15+u-22=9/2 | | p(1-.105)=5907 | | 2a+6b=30 | | 4x-4/2x-2 | | -2?7=-3+t+24 | | x+.105x=5907 | | 75X-100y=400 | | 3x-8(-3x+5x)=24 | | ((8x/x^3-x^6/x^3))^-4/5 | | 4cos^2x+3secx-3-4cosx=0 | | -3.33333333333b=5 |